RECOVERY MEASURES TAKEN BY SARAWAK STATE GOVERNMENT TO OVERCOME THE CHALLENGES OF HAWKERS DURING THE COVID- 19 PANDEMIC - Anisa Safiqah Othman; Noni Harianti Junaidi; Kuldip Singh (International Journal of Accounting, Finance and Business, 2021)
COVID-19 widespread was perceived in December 2019 in Wuhan, China and it has spread over the world through the development of the individuals. In Malaysia cases of the infection extended significantly since March 2020. The development of the disease and its economic impact is however unpredictable. It is challenging for policymakers to formulate a macroeconomic policy that is appropriate for every sectors and the people in the country. After the shifting of government within the of widespread, government Malaysia took prompt response by implemented lockdown measure all through the nation. The lockdown moreover had its own socio-economic impact because it deferred most economic activities and operations with an exception of essential services. This paper anticipated to observe the impact and recovery measure of COVID-19 on informal workers in Sarawak. Qualitative method is used in this study and data was collected using structured interview from September to October 2020 with 10 street vendors. Interviews were then transcribed and thematic analysis was adapted in analysing the data. The informal sector, in spite of the fact that not formally recorded as a contributor to GDP, it was established that there are critical impacts on this sector deriving from the daily loss of income due to lockdown measures. The loss of income indirectly affect employment in the nation since these individuals become concisely unemployed, thus a reduction in domestic consumption.